2021
DOI: 10.4038/sljpsyc.v12i2.8320
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity and resilience associated with tinnitus in a Sri Lankan population

Abstract: ObjectiveTinnitus is a common and debilitating health condition. It is often associated with psychiatric morbidity. This important health concern has not been studied previously in Sri Lanka. We aimed to determine the prevalence of psychological morbidity, resilience and their correlates among a cohort of Sri Lankan patients with tinnitus. MethodsA descriptive cross-sectional study was conducted among attendees of otolaryngology clinics in three Sri Lankan hospitals, using a specially designed questionnaire. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Psyhological morbidity reported in this sample is similar to the prevalence reported in Sri Lankan and international studies conducted in individuals with tinntius [6,[19][20][21][22][23][24][25][26][27][28]. Severity of tinnitus in our sample is largely similar to other validation studies [20,28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Psyhological morbidity reported in this sample is similar to the prevalence reported in Sri Lankan and international studies conducted in individuals with tinntius [6,[19][20][21][22][23][24][25][26][27][28]. Severity of tinnitus in our sample is largely similar to other validation studies [20,28].…”
Section: Discussionsupporting
confidence: 88%
“…Severe annoyance associated with tinnitus is linked to increased suicide [2]. While prevalence of tinnitus in Sri Lanka is not known, it is estimated that least 2 million Sri Lankans experience tinnitus during their lifetime [6]. A Sri Lankan study found that 82.5% reported functional impairment due to tinnitus and 61.5% were found to have depression [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation